Biglycan Regulates MG63 Osteosarcoma Cell Growth Through a LPR6/β-Catenin/IGFR-IR Signaling Axis - Aggelidakis, John; Berdiaki, Aikaterini; Nikitovic, Dragana; Papoutsidakis, Antonis; Papachristou, Dionysios J.; Tsatsakis, Aristidis M.; Tzanakakis, George N. (Frontiers in Oncology, 2018)
Biglycan, a small leucine rich proteoglycan (SLRP), is an important participant in bone homeostasis and development as well as in bone pathology. In the present study biglycan was identified as a positive regulator of MG63 osteosarcoma cell growth (p≤ 0.001). IGF-I was shown to increase biglycan expression (p≤ 0.01), whereas biglycan-deficiency attenuated significantly both basal and IGF-I induced cell proliferation of MG63 cells (p≤ 0.001; p≤ 0.01 respectively). These effects were executed through the IGF-IR receptor whose activation was strongly attenuated (p≤ 0.01) in biglycan-deficient MG63 cells. Biglycan, previously shown to regulate Wnt/β-catenin pathway, was demonstrated to induce a significant increase in β-catenin protein expression evident at cytoplasmic (p≤ 0.01), membrane (p≤ 0.01), and nucleus fractions in MG63 cells (p≤ 0.05). As demonstrated by immunofluorescence, increase in β-catenin expression is attributed to co-localization of biglycan with the Wnt co-receptor low-density lipoprotein receptor-related protein 6 (LRP6) resulting in attenuated β-catenin degradation. Furthermore, applying anti-β-catenin and anti-pIGF-IR antibodies to MG-63 cells demonstrated a cytoplasmic and to the membrane interaction between these molecules that increased upon exogenous biglycan treatment. In parallel, the downregulation of biglycan significantly inhibited both basal and IGF-I-dependent ERK1/2 activation, (p≤ 0.001). In summary, we report a novel mechanism where biglycan through a LRP6/β-catenin/IGF-IR signaling axis enhances osteosarcoma cell growth.